Virtus Romana en el siglo I a.C. - Balmaceda , Catalina (Gerión. Revista de Historia Antigua, 2008)
Analysing the etymology and original usage of the word virtus and the complex connections with its Greek parallels andreia and areté will take us to argue in this article that the deep Roman meaning of the concept was used for Roman self-definition and it played a special role in politics. I shall then deal with the idea of the ‘expansion of the concept’ in a twofold way: its broader range of meaning and its wider appeal to different sectors of society. The meeting of the Greek and Roman cultures will also be addressed here and I will discuss the development of a philosophical definition of the concept of virtus and the Stoic application of it to Roman society in the first century BC mainly through Cicero’s writings.